Imperforate nasopharynx in a cat successfully treated with an extended palatoplasty - Michal O Hess (Journal of Feline Medicine and Surgery Open Reports)
Case summary A female intact domestic shorthair kitten was evaluated at 8 months of age for bilateral mucopurulent nasal discharge, stertor, open-mouth breathing and difficulty eating. Imperforate nasopharynx (INP) was diagnosed on oronasal examination under anesthesia. An extended palatoplasty was performed and resulted in resolution of the clinical signs. Relevance and novel information The extended palatoplasty procedure is relatively simple and very similar to the correction of soft palate elongation in brachycephalic dogs. It does not require special equipment and materials; therefore, it represents a viable, more readily available and cost-effective option for the treatment of INP. To the author’s knowledge, this is the first case of INP that has been treated with extended palatoplasty.